Euthanasia – right to die with dignity - Mohd Hussain, Azlina; Ngah, Nor Syamaliah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Assisted dying refers to procedures intended to end a person’s life out of compassion, typically for those with terminal illnesses and severe suffering, and includes both assisted suicide—where a patient self-administers prescribed lethal medication—and euthanasia, where another person administers it. Although often used interchangeably, the key difference lies in who performs the final act. In many legal systems, assisted dying is treated as suicide or murder due to the absence of specific laws, while in some jurisdictions it is legally permitted under strict conditions requiring voluntary consent. Terminology varies globally, such as euthanasia, assisted suicide, or medical assistance in dying, depending on the country.